Lithium-deficient and halide-rich solid electrolyte
By developing lithium-deficient and halide-rich solid electrolytes, the safety hazards and poor low-temperature performance of liquid electrolytes in lithium secondary batteries are solved, high ionic conductivity and good moisture stability are achieved, and the battery's performance is improved. Security and performance.
Patent Information
- Application Number
- CN202380048218.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-24
- Filing Date
- 2023-06-20
- Publication Date
- 2025-01-24
AI Technical Summary
The liquid electrolytes in existing lithium secondary batteries have safety risks, such as the risk of leakage and fire, and their performance is poor under low temperature conditions.
It has developed a solid electrolyte with lithium deficiency and halogen. Its chemical formula is LI6-YPS5-YBRXY, 0.0
The high ion conductivity of solid electrolytes is achieved, especially at low temperatures showing excellent conductive properties, and significantly reduced H2S gases when they contact with water, and improved the feasibility of its commercial production and use.
Smart Images

Figure CN119366019A_ABST
Abstract
Description
Technical Field and Background Art
[0001] The present invention relates to a lithium-deficient and halide-rich solid electrolyte, a method for producing the solid electrolyte and a battery comprising the solid electrolyte.
[0002] As the development of small and lightweight electronic products, electronic equipment, communication equipment, etc. has rapidly progressed, and the demand for electric vehicles has widely emerged in terms of environmental issues, there is a demand for improving the performance of secondary batteries used as power sources for these products. Among these secondary batteries, lithium secondary batteries have become the focus of high-performance batteries due to their high energy density and high reference electrode potential.
[0003] However, the electrolyte conventionally used in lithium secondary batteries is a liquid electrolyte made of a lithium salt dissolved in an organic solvent. Therefore, safety problems such as leakage of the electrolyte and the risk of fire may continue to occur.
[0004] Recently, solid-state batteries including solid electrolytes instead of liquid electrolytes have been used to improve the safety characteristics of lithium secondary batteries and have attracted much attention. For example, solid electrolytes are generally safer than liquid electrolytes due to non-flammable or flame-retardant properties.
[0005] The solid electrolyte may include an oxide-based solid electrolyte, a polymer-based electrolyte, and a sulfide-based electrolyte. Since the sulfide-based electrolyte has a higher lithium ion conductivity range than the oxide-based solid electrolyte and the polymer-based solid electrolyte, a sulfide-based electrolyte, such as a sulfide-based solid electrolyte having an argyrodite-type crystal structure, is generally used.
[0006] WO2020 / 033809 A1 and Patel et al. (Chem. Mater. 2021, 33, 4, 1435–1443) describe the synthesis of lithium-deficient halide-rich solid electrolytes having the general formula Li 6-ω PS 5-ω Cl 1.0 Br ω , where 0≤ω≤0.7, such as Li 5.7 PS 4.7 Cl 1.0 Br 0.3 and Li 5.5 PS 4.5 Cl 1.0 Br 0.5。
[0007] The object of the present invention is to provide a solid electrolyte which is deficient in lithium and rich in halides.
[0008] Another object of the present invention is to provide a method for manufacturing the solid electrolyte.
[0009] Another object of the present invention is to provide a battery comprising the solid electrolyte. SUMMARY OF THE INVENTION
[0010] In a first aspect, the object of the present invention is achieved by providing a solid electrolyte having a composition according to formula (I):
[0011] Li 6-y PS 5-y BrX y (I),
[0012] where 0.0 < y < 0.8, and X is F, Cl, I or a combination thereof.
[0013] The inventors have surprisingly found that these lithium-deficient halide-rich solid electrolyte compositions exhibit an increased ionic conductivity of up to 9.9 mS·cm -1 , as demonstrated in the appended examples. In particular, high conductivity is even measured at low temperatures, making these compositions suitable for low-temperature applications. In addition, these solid electrolyte compositions according to the present invention show a reduced evolution of H2S gas upon contact with moisture, making them more attractive for commercial production and use in batteries.
[0014] Without wishing to be bound by any theory, the inventors believe that the X - / S 2- site disorder is increased by an excess and / or mixed halide substitution, thereby affecting the lithium substructure by changing the Li 2- site positions due to the electrostatic difference between S - and X + . Furthermore, when a sulfide electrolyte containing PS4 tetrahedra reacts with moisture, the sulfur in PS4 is replaced by oxygen, thereby generating H2S gas. This poor moisture stability of known thiospinels (such as Li6PS5Br and Li6PS5Cl) can be mainly attributed to the oxygenophilic nature of phosphorus. However, substituting S 2- in the composition with halides results in a reduced evolution of H2S, as demonstrated in the appended examples.
[0015] In a further aspect, the present invention provides a method for manufacturing the solid electrolyte.
[0016] The inventors have surprisingly found that an electrolyte precursor mixture containing stoichiometric ratios of Li2S, P2S5, LiBr and LiCl needs to be ball milled for at least 0.5 hours. WO2020 / 033809 A1 teaches that the disclosed solid electrolyte composition, such as Li2S, P2S5, LiBr and LiCl, is obtained after ball milling for 10 minutes. 5.7 PS 4.7 Cl 1.0 Br 0.3 and Li 5.7 PS 4.7 Cl 1.0 I 0.3 However, these ball milling conditions, especially the ball milling time of the solid electrolyte precursor, are not sufficient to obtain the solid electrolyte composition according to the present invention.
[0017] In a further aspect, the present invention provides a battery comprising the solid electrolyte according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1a : Li recorded at 298 K in a beryllium-capped sealed chamber 6-x PS 5-x Br 1.0 Cl x X-ray diffraction pattern of , where nominal x = 0, 0.1, 0.3, 0.5, 0.7 and 0.8.
[0019] Figure 1b : Li between 2θ=43° and 48° 6-x PS 5-x Br 1.0 Cl x A magnified region of , where nominally x = 0.0, 0.1, 0.3, 0.5, 0.7, and 0.8.
[0020] Figure 2 : Li recorded at 298K after annealing at 450°C 5.5 PS 4.5 Br 1.5-x Cl x X-ray diffraction patterns of (x=0, 0.5, 1.0, 1.5).
[0021] Figure 3 :With Li 6-x PS 5-x Br 1.0 Cl x The change of lattice constant a with the increase of x, where x=0, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7 and 0.8.
[0022] Figure 4a :Li6-x PS 5-x BrCl x Raman spectra of (x=0.0, 0.1, 0.3, 0.5, 0.7 and 0.8)
[0023] Figure 4b : 360cm -1 and 480cm -1 Li 6-x PS 5-x BrCl x Detailed Raman spectra of (x = 0.0, 0.1, 0.3, 0.5, 0.7, and 0.8).
[0024] Figure 5 :per liter of air and per gram of Li6PS5Br, Li6PS5Cl, Li 5.3 PS 4.3 BrCl 0.7 , Li 5.5 PS 4.5 BrCl 0.5 and Li 5.7 PS 4.7 BrCl 0.3 The generated H2S.
[0025] Figure 6 : Rate performance of EX8 and CEX6.
[0026] Figure 7 : Long cycle stability of cells containing cathode composites with 60 wt%, 70 wt%, 80 wt% and 88 wt% NMC 622 cycled at C / 5. DETAILED DESCRIPTION
[0027] In the accompanying drawings and the following detailed description, preferred embodiments are described in detail to practice the present invention. Although the present invention is described with reference to these specific preferred embodiments, it should be understood that the present invention is not limited to these preferred embodiments. On the contrary, the present invention includes many alternatives, modifications and equivalent forms, which will become apparent by considering the following detailed description and the accompanying drawings.
[0028] As used herein and in the claims, the term "comprising" should not be interpreted as being limited to the means listed thereafter; it does not exclude other elements or steps. It needs to be interpreted as specifying the presence of the features, integers, steps or components mentioned, but does not exclude the presence or addition of one or more other features, integers, steps or components or groups thereof. Therefore, the scope of the expression "a composition comprising component A and component B" should not be limited to a composition consisting only of component A and component B. This means that with respect to the present invention, the only relevant components of the composition are A and B. Therefore, the terms "comprising" and "including" encompass the more restrictive terms "consisting essentially of" and "consisting of".
[0029] As used herein, the term "solid-state battery" refers to a battery cell or battery that includes only solid-state components or substantially solid-state components such as solid electrodes (eg, anodes and cathodes) and a solid electrolyte.
[0030] As used herein, the term "argyrodite crystal structure" refers to a crystal structure having a crystal structure or system similar to the naturally occurring Ag8GeS6 and Li7S6 (argyrodite). The argyrodite crystal structure can be orthorhombic symmetric, but is more likely cubic symmetric and is described in the F-43m space group. In some embodiments, the argyrodite crystal structure can also be determined empirically, for example, by observing diffraction peaks around 2θ=15.5±1°, 18±1°, 26±1°, 30.5±1° and 32±1° using CuKα-ray wavelengths, and by X-ray diffraction spectroscopy.
[0031] X-ray diffraction (XRD) as referred to herein refers to XRD experiments performed using a Bruker D8 diffractometer equipped with Cu (Kα1-Kα2) or Mo (Kα1-Kα2) radiation in the θ-θ configuration.
[0032] Preferably, a gas-tight sample holder covered with a Be window (mostly transparent to X-rays) is used. Preferably, patterns are collected between 2θ = 10° - 70° with a step size of 0.02°.
[0033] Raman spectroscopy as referred to herein refers to Raman experiments performed using a Raman DXR microscope (Thermo Fischer Scientific) equipped with a green laser with an excitation wavelength of 532 nm. Preferably, a laser power of 0.1 mW is used to avoid sample damage due to excessive local heating. Preferably, the spectrum is collected with a 1 second exposure time and 180 exposures.
[0034] Unless otherwise described, ionic conductivity as referred to herein refers to ionic conductivity determined at 25°C. Preferably, the ionic conductivity is determined on a cold pressed sample in a 10 mm die using a BioLogic CESH cell at 625 MPa, and the spectrum is recorded using a MTZ 35 frequency response analyzer by applying a 50 mV AC perturbation in a frequency range of 30 MHz to 1 Hz. Preferably, the relative density of the pellets is 85% to 87%, and the thickness is approximately 1.4 mm. Preferably, indium foil is pressed on the surface of the pellets as an ion blocking electrode. More preferably, the spectrum is collected between a temperature range of -20°C to 50°C in an ITS temperature controller at 10°C intervals.
[0035] As referred to herein, moisture stability refers to the amount of H2S recorded every 20 seconds, in ppm, for 20 minutes, measured with a H2S sensor (Model-INS-H2S-03 (0 ppm-400ppm, 20%-90%RH)). Preferably, approximately 45 mg of powder is granulated in a 10 mm die, and the granules are placed on a rectangular polymer container in a desiccator, and the lid of the desiccator is closed. The number of moles of H2S generated per liter of ambient air and per gram of sample is calculated using the following equation:
[0036]
[0037] As will be appreciated by those skilled in the art, the composition according to formula (I), in particular the bromine content present in the composition according to formula (I), has the following stoichiometric ratio:
[0038] Li 6-y PS 5-y BX y (I) = Li 6-y PS 5-y Br 1.0 X y (I)'
[0039] As used herein, the term "solid electrolyte precursor mixture" refers to an electrolyte precursor mixture that is substantially free of any liquid. The term "substantially free of liquid" means that, by the total weight of the solid electrolyte precursor mixture, the solid electrolyte precursor mixture contains less than 10% by weight of liquid, preferably, by the total weight of the solid electrolyte precursor mixture, the solid electrolyte precursor mixture contains less than 7.5% by weight, more preferably less than 5% by weight, even more preferably less than 2.5% by weight, and most preferably less than 1% by weight of liquid. In a more preferred embodiment, by the total weight of the solid electrolyte precursor mixture, the solid electrolyte precursor mixture contains less than 1000ppm of liquid, preferably, by the total weight of the solid electrolyte precursor mixture, the solid electrolyte precursor mixture contains less than 500ppm, more preferably less than 100ppm, even more preferably less than 50ppm, and most preferably less than 10ppm of liquid.
[0040] In the context of the present invention, a liquid is considered to be an organic or aqueous compound that is liquid under standard temperature and pressure conditions defined by IUPAC. Accordingly, boiling points and melting points are considered to be boiling points and melting points under standard atmospheric pressure, i.e., 101325 Pa. As will be appreciated by those skilled in the art, the presence of an organic liquid can be determined via thermogravimetric analysis (TGA) or nuclear magnetic resonance (NMR) spectroscopy, and the presence of an aqueous liquid can be determined via Karl Fisher titration.
[0041] As used herein, the term "solid electrolyte mixture" refers to an electrolyte mixture that is substantially free of any liquid. The term "substantially free of liquid" means that, by the total weight of the solid electrolyte mixture, the solid electrolyte mixture comprises less than 10% by weight of liquid, preferably, by the total weight of the solid electrolyte mixture, the solid electrolyte mixture comprises less than 7.5% by weight, more preferably less than 5% by weight, even more preferably less than 2.5% by weight, and most preferably less than 1% by weight of liquid. In a more preferred embodiment, by the total weight of the solid electrolyte mixture, the solid electrolyte mixture comprises less than 1000ppm of liquid, preferably, by the total weight of the solid electrolyte mixture, the solid electrolyte mixture comprises less than 500ppm, more preferably less than 100ppm, even more preferably less than 50ppm, and most preferably less than 10ppm of liquid.
[0042] As used herein, the term "solid electrolyte" refers to an electrolyte that is substantially free of any liquid. The term "substantially free of liquid" means that the solid electrolyte contains less than 10% by weight of liquid, based on the total weight of the solid electrolyte. Preferably, the solid electrolyte contains less than 7.5% by weight, more preferably less than 5% by weight, even more preferably less than 2.5% by weight, and most preferably less than 1% by weight of liquid, based on the total weight of the solid electrolyte. In a more preferred embodiment, the solid electrolyte precursor contains less than 1000 ppm of liquid, based on the total weight of the solid electrolyte. Preferably, the solid electrolyte contains less than 500 ppm, more preferably less than 100 ppm, even more preferably less than 50 ppm, and most preferably less than 10 ppm of liquid, based on the total weight of the solid electrolyte.
[0043] Solid electrolyte
[0044] In a first aspect, the present invention provides a solid electrolyte having a composition according to formula (I):
[0045] Li 6-y PS 5-y BrX y (I),
[0046] where 0.0 < y < 0.8, and X is F, Cl, I, or a combination thereof.
[0047] In a preferred embodiment, the solid electrolyte is according to the present invention, wherein 0.01 ≤ y ≤ 0.79, preferably 0.05 ≤ y ≤ 0.75, more preferably 0.075 ≤ y ≤ 0.725, even more preferably 0.09 ≤ y ≤ 0.71, and most preferably 0.1 ≤ y ≤ 0.7. In a particularly preferred embodiment, the solid electrolyte is according to the present invention, wherein 0.4 ≤ y ≤ 0.7, preferably 0.5 ≤ y ≤ 0.7, more preferably 0.55 ≤ y ≤ 0.65.
[0048] In a particularly preferred embodiment, the solid electrolyte is according to the present invention, wherein 0.01 ≤ y ≤ 0.59, preferably 0.05 ≤ y ≤ 0.55, more preferably 0.075 ≤ y ≤ 0.52, even more preferably 0.09 ≤ y ≤ 0.51, and most preferably 0.1 ≤ y ≤ 0.5.
[0049] In a particularly preferred embodiment, the solid electrolyte is according to the present invention, wherein X is F, Cl, I, or a combination thereof; preferably X is a combination of Cl, I, or both; preferably X is Cl.
[0050] In a particularly preferred embodiment, the solid electrolyte is according to the present invention, wherein X is F, Cl, or I; preferably X is Cl or I; preferably X is Cl.
[0051] According to a preferred embodiment of the present invention, a solid electrolyte is provided, wherein at least 50 mol % of X represents Cl, preferably at least 80 mol % of X represents Cl, most preferably X represents Cl.
[0052] According to a preferred embodiment of the present invention, a solid electrolyte is provided, wherein X represents Cl, F, I or a combination thereof, and wherein at least 50 mol % of X represents Cl, preferably at least 80 mol % of X represents Cl.
[0053] According to a preferred embodiment of the present invention, a solid electrolyte is provided, wherein at least 50 mol % of X represents F, preferably at least 80 mol % of X represents F, and most preferably X represents F.
[0054] According to a preferred embodiment of the present invention, a solid electrolyte is provided, wherein X represents Cl, F, I or a combination thereof, and wherein at least 50 mol % of X represents F, preferably at least 80 mol % of X represents F.
[0055] According to a preferred embodiment of the present invention, a solid electrolyte is provided, wherein at least 50 mol % of X represents I, preferably at least 80 mol % of X represents I, and most preferably X represents I.
[0056] According to a preferred embodiment of the present invention, a solid electrolyte is provided, wherein X represents Cl, Br, I or a combination thereof, and wherein at least 50 mol % of X represents I, preferably at least 80 mol % of X represents I.
[0057] In a particularly preferred embodiment, the solid electrolyte is according to the invention, wherein
[0058] •X is Cl, and
[0059] • 0.01≤y≤0.79, preferably 0.09≤y≤0.71, most preferably 0.1≤y≤0.7.
[0060] In a particularly preferred embodiment, the solid electrolyte is according to the invention, wherein
[0061] •X is Cl, and
[0062] • 0.4≤y≤0.7, preferably 0.5≤y≤0.7, most preferably 0.55≤y≤0.65.
[0063] In a particularly preferred embodiment, the solid electrolyte is according to the invention, wherein
[0064] •X is Cl, and
[0065] • wherein 0.01 ≤ y ≤ 0.59, preferably 0.05 ≤ y ≤ 0.55, more preferably 0.075 ≤ y ≤ 0.52, even more preferably 0.09 ≤ y ≤ 0.51, and most preferably 0.1 ≤ y ≤ 0.5.
[0066] In a particular preferred embodiment, the solid electrolyte is according to the present invention, wherein
[0067] • X is I, and
[0068] • 0.0 < y < 0.5, preferably 0.01 ≤ y ≤ 0.49, more preferably 0.05 ≤ y ≤ 0.45, even more preferably 0.09 ≤ y ≤ 0.41, and most preferably 0.1 ≤ y ≤ 0.4.
[0069] In a particular preferred embodiment, the solid electrolyte is according to the present invention, wherein
[0070] • X is I, and
[0071] • 0.05 ≤ y ≤ 0.35, preferably 0.075 ≤ y ≤ 0.325, more preferably 0.1 ≤ y ≤ 0.3.
[0072] In a more preferred embodiment, the solid electrolyte is according to the present invention, wherein the solid electrolyte is according to formula (I) a - g.
[0073]
[0074] In a preferred embodiment, the solid electrolyte is according to the present invention, having the F - 43m space group, preferably having a lattice parameter a (Å) between 10.00 and 9.90, preferably between 9.99 and 9.91, more preferably between 9.985 and 9.915, determined by least - squares refinement and / or Rietveld analysis of the XRD curve.
[0075] In a preferred embodiment, the solid electrolyte is according to the present invention, having a thiogermanate crystal structure.
[0076] In a preferred embodiment, the solid electrolyte is according to the present invention, wherein the molar ratio of Li:P:S:Br:X is between (5-6):(0.9-1.1):(4-5):(0.9-1.1):(0.01-0.79), preferably (5.1-5.9):(0.91-1.09):(4.1-4.9):(0.91-1.09):(0.05-0.75), more preferably (5.29-5.91):(0.99-1.01):(4.29-4.91):(0.99-1.01):(0.09-0.71), and most preferably (5.3-5.9):1:(4.3-4.9):1:(0.1-0.7).
[0077] In a preferred embodiment, the solid electrolyte is according to the invention, having a conductivity between 1 mS / cm and 12 mS / cm, preferably between 2 mS / cm and 10 mS / cm, most preferably between 6 mS / cm and 10 mS / cm.
[0078] In a particularly preferred embodiment, the solid electrolyte is according to the invention, wherein
[0079] •X is Cl;
[0080] • 0.4≤y≤0.7, preferably 0.5≤y≤0.7, most preferably 0.55≤y≤0.65; and
[0081] • Solid electrolyte has 5mS.cm -1 and 12mS.cm -1 Between, preferably 5.5mS.cm -1 and 11mS.cm -1 Between, most preferably 6mS.cm -1 and 10mS.cm -1 The conductivity between.
[0082] In a particularly preferred embodiment, the solid electrolyte is according to the invention, wherein
[0083] • The solid electrolyte is Li 5.5 PS 4.5 BrCl 0.5 ,and
[0084] • Solid electrolyte has a 0.1mS.cm -1 and 1.9mS.cm -1 Between, preferably between 0.5mS.cm -1 and 1.5mS.cm -1 Between, most preferably about 1mS.cm -1 The conductivity is measured at -20°C.
[0085] In a preferred embodiment, the solid electrolyte is according to the invention having a purity of at least 90%, preferably at least 95%, more preferably at least 99% as determined by XRD.
[0086] In a preferred embodiment, the solid electrolyte is according to the invention and has a -1 and 430cm -1 Between, preferably between 421cm -1 and 429cm -1 Between, preferably between 422cm -1 and 428cm -1 peaks between, as determined by Raman spectroscopy.
[0087] In a preferred embodiment, the solid electrolyte is according to the present invention and has good water stability, in particular, the solid electrolyte generates or releases less than 5.0 mmol.L after 15 minutes. -1 .g -1 of H2S, preferably less than 4.5 mmol.L generated or released after 15 minutes as determined by water stability -1 .g -1 More preferably, less than 4.0 mmol.L of H2S is generated or released after 15 minutes as determined by water stability. -1 .g -1 of H2S.
[0088] Manufacturing method
[0089] In a second aspect, the present invention provides a method for manufacturing a solid electrolyte, the method comprising the steps of:
[0090] a) providing a solid electrolyte precursor mixture comprising Li2S, P2S5, LiBr and LiX;
[0091] b) mixing the solid electrolyte precursor mixture to obtain a solid electrolyte mixture; and
[0092] c) heat treating the solid electrolyte mixture to obtain a solid electrolyte;
[0093] wherein X is a halogen selected from F, Cl, I or a combination thereof, preferably X is selected from Cl, I or a combination thereof, most preferably X is Cl.
[0094] In a highly preferred embodiment, the method is according to the invention wherein the solid electrolyte is according to the first aspect of the invention.
[0095] As understood by those skilled in the art, all embodiments related to the solid electrolyte according to the first aspect of the present invention are equally applicable to the method for manufacturing the solid electrolyte according to the present invention.
[0096] In a preferred embodiment, the method is according to the invention, wherein the mixing of the solid electrolyte precursor of step b) lasts for at least 15 minutes, preferably at least 0.5 hours, most preferably at least 1 hour.
[0097] In a preferred embodiment, the process is according to the invention, wherein the mixing of the solid electrolyte precursor of step b) is between 1 hour and 60 hours, preferably between 5 hours and 45 hours, most preferably between 10 hours and 30 hours.
[0098] In a preferred embodiment, the method is according to the present invention, wherein the mixing of the solid electrolyte precursor of step b) has a mixing speed of 100 rpm-1000 rpm, preferably a mixing speed of 300 rpm-900 rpm, most preferably a mixing speed of 400 rpm-800 rpm.
[0099] In a preferred embodiment, the method is according to the invention, wherein the mixed solid electrolyte precursor mixture of step b) is carried out at a temperature of at least 5° C., preferably at least 10° C., more preferably at least 15° C. A preferred embodiment is the method according to the invention, wherein the mixed solid electrolyte precursor mixture of step b) is carried out at a temperature of less than 50° C., preferably less than 40° C., more preferably less than 30° C. A preferred embodiment is the method according to the invention, wherein the mixed solid electrolyte precursor mixture of step b) is carried out at a temperature between 5° C. and 50° C., preferably between 10° C. and 40° C., more preferably between 15° C. and 30° C.
[0100] In a particularly preferred embodiment, the method according to the invention is wherein the mixed solid electrolyte precursor of step b)
[0101] • having a mixing time of between 1 hour and 60 hours, preferably between 5 hours and 45 hours, most preferably between 10 hours and 30 hours; and
[0102] • Having a mixing speed of 100-1000 rpm, preferably a mixing speed of 300-900 rpm, most preferably a mixing speed of 400-800 rpm.
[0103] In a particularly preferred embodiment, the method is according to the invention, wherein step b) comprises
[0104] b1) Mixing the solid electrolyte precursor mixture to obtain a solid electrolyte premixture
[0105] • having a mixing time of between 1 minute and 10 hours, preferably between 5 minutes and 5 hours, most preferably between 15 minutes and 3 hours; and
[0106] • Having a mixing speed of 1 rpm-500 rpm, preferably a mixing speed of 50 rpm-300 rpm, most preferably a mixing speed of 100 rpm-200 rpm.
[0107] b2) Mixing the solid electrolyte premix to obtain a solid electrolyte mixture
[0108] • having a mixing time of between 1 hour and 60 hours, preferably between 5 hours and 45 hours, most preferably between 10 hours and 30 hours; and
[0109] • Having a mixing speed of 100-1000 rpm, preferably a mixing speed of 300-900 rpm, most preferably a mixing speed of 400-800 rpm.
[0110] In a preferred embodiment, the method is according to the invention, wherein the heat treatment of the solid electrolyte mixture in step c) is carried out at a temperature of at least 100° C., preferably at least 200° C., more preferably at least 300° C., even more preferably at least 350° C., most preferably at least 400° C. In a preferred embodiment, the method is according to the invention, wherein the heat treatment of the solid electrolyte mixture in step c) is carried out at a temperature of less than 1000° C., preferably less than 900° C., more preferably less than 750° C., even more preferably less than 600° C., most preferably less than 500° C. In a preferred embodiment, the method is according to the invention, wherein the heat treatment of the solid electrolyte mixture in step c) is carried out at a temperature between 100° C. and 1000° C., preferably between 300° C. and 750° C., more preferably between 450° C. and 550° C.
[0111] In a preferred embodiment, the method is according to the present invention, wherein the heat treatment of the solid electrolyte mixture in step c) is at least 1 minute, preferably at least 0.5 hours, more preferably at least 1 hour, even more preferably at least 1.5 hours, even more preferably at least 2 hours. In a preferred embodiment, the method is according to the present invention, wherein the heat treatment of the solid electrolyte mixture in step c) is less than 48 hours, preferably less than 24 hours, more preferably less than 18 hours, even more preferably less than 12 hours, even more preferably less than 10 hours. In a preferred embodiment, the method is according to the present invention, wherein the heat treatment of the solid electrolyte mixture in step c) is between 0.5 hours and 24 hours, preferably between 1 hour and 12 hours, more preferably between 1.5 hours and 10 hours.
[0112] In a particularly preferred embodiment, the method is according to the invention, wherein step c) of heat treating the solid electrolyte mixture
[0113] • at a temperature between 100°C and 1000°C, preferably between 300°C and 750°C, most preferably between 450°C and 550°C; and
[0114] • Between 0.5 hours and 24 hours, preferably between 1 hour and 12 hours, most preferably between 1.5 hours and 10 hours.
[0115] Composite positive electrode active materials
[0116] A third aspect of the present invention relates to a composite positive electrode active material comprising a positive electrode active material and the solid electrolyte according to the first aspect of the present invention.
[0117] As used herein and in the claims, the term "positive electrode active material" (also referred to as cathode active material) is defined as a material that is electrochemically active in the positive electrode or cathode. By active material, it must be understood that the material is capable of capturing and releasing lithium ions when subjected to a voltage change over a predetermined period of time.
[0118] In a preferred embodiment, the positive electrode active material (also referred to as the cathode active material) comprises Li, M and O, wherein M comprises one or both of Mn and Co and Ni. Preferably, the cathode active material comprises Li, M and O, wherein M comprises
[0119] - Ni with a content of x, wherein relative to M, 50.0mol%≤x≤95.0mol%;
[0120] - Mn with a content of y, wherein 0.0 mol%≤y≤40.0 mol% relative to M;
[0121] - Co with a content of z, wherein relative to M, 0.0mol%≤z≤40.0mol%;
[0122] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0123] - wherein x+y+z+a is 100.0 mol%;
[0124] More preferably wherein M comprises:
[0125] - Ni with a content of x, wherein relative to M, 55.0mol%≤x≤85.0mol%;
[0126] - Mn with a content of y, wherein relative to M, 10.0 mol%≤y≤30.0 mol%;
[0127] - Co with a content of z, wherein relative to M, 10.0mol%≤z≤30.0mol%;
[0128] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0129] - wherein x+y+z+a is 100.0 mol%;
[0130] Most preferably wherein M comprises:
[0131] - Ni with a content of x, wherein 58.0mol%≤x≤70.0mol% relative to M;
[0132] - Mn with a content of y, wherein relative to M, 15.0mol%≤y≤25.0mol%;
[0133] - Co with a content of z, wherein relative to M, 15.0mol%≤z≤25.0mol%;
[0134] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0135] - wherein x+y+z+a is 100.0 mol%.
[0136] In some particularly preferred embodiments, x is about 60 mol%, y is about 20 mol%, and z is about 20 mol%. This is also known as NMC 622.
[0137] In a preferred embodiment of the present invention, D is at least one element selected from the group consisting of Al, Ti, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, V, W, Y, Zn and Zr; preferably Al, B, Ti, Cr, Nb, S, Si, Y, Zr and W; more preferably Al, B, Ti, Nb, Zr and W.
[0138] In some particularly preferred embodiments, a=0.0 mol %.
[0139] In a preferred embodiment, the Li / M ratio (mol / mol) is between 0.9 and 1.1, preferably between 0.95 and 1.05, more preferably between 0.99 and 1.01, most preferably about 1.
[0140] As understood by those skilled in the art, the amount of Li and M in the positive electrode active material, preferably the amount of Li, Ni, Mn and Co, is measured by inductively coupled plasma optical emission spectroscopy (ICP-OES). For example, but not limited to the present invention, an Agilent ICP 720-ES is used in the ICP-OES analysis.
[0141] In a particularly preferred embodiment, the solid electrolyte is according to formula (I), wherein 0.4≤y≤0.7, preferably 0.5≤y≤0.7, more preferably 0.55≤y≤0.65. In a particularly preferred embodiment, the solid electrolyte is according to formula (I)f.
[0142] In certain preferred embodiments, the solid electrolyte is according to formula (I), wherein 0.01≤y≤0.59, preferably 0.05≤y≤0.55, more preferably 0.075≤y≤0.52, even more preferably 0.09≤y≤0.51, most preferably 0.1≤y≤0.5.
[0143] In a preferred embodiment, the composite positive electrode active material comprises
[0144] - between 55% and 95% by weight of positive electrode active material, based on the total weight of the composite positive electrode active material, preferably between 65% and 85% by weight of positive electrode active material, based on the total weight of the composite positive electrode active material, more preferably between 65% and 75% by weight of positive electrode active material, based on the total weight of the composite positive electrode active material; and
[0145] - between 5% and 55% by weight of the solid electrolyte according to the first aspect of the present invention, based on the total weight of the composite positive electrode active material, preferably between 15% and 35% by weight of the solid electrolyte according to the first aspect of the present invention, based on the total weight of the composite positive electrode active material, more preferably between 25% and 35% by weight of the solid electrolyte according to the first aspect of the present invention, based on the total weight of the composite positive electrode active material.
[0146] In a highly preferred embodiment, the composite positive electrode active material of the invention comprises a positive electrode active material as defined herein and a solid electrolyte according to the first aspect of the invention,
[0147] The positive electrode active material comprises Li, M and O, wherein M comprises:
[0148] - Ni with a content of x, wherein 58.0mol%≤x≤70.0mol% relative to M;
[0149] - Mn with a content of y, wherein relative to M, 15.0mol%≤y≤25.0mol%;
[0150] - Co with a content of z, wherein relative to M, 15.0mol%≤z≤25.0mol%;
[0151] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0152] - wherein x+y+z+a is 100.0 mol%, and
[0153] The solid electrolyte is according to formula (I), wherein 0.4≤y≤0.7, preferably 0.5≤y≤0.7, more preferably 0.55≤y≤0.65.
[0154] In a highly preferred embodiment, the composite positive electrode active material of the invention comprises a positive electrode active material as defined herein and a solid electrolyte according to the first aspect of the invention, wherein the positive electrode active material comprises Li, M and O, wherein M comprises:
[0155] - Ni with a content of x=60 mol% relative to M;
[0156] - Mn with a content of y=20 mol% relative to M;
[0157] - Co in an amount z=20 mol% relative to M; and
[0158] wherein the solid electrolyte is according to formula (I)f.
[0159] Battery
[0160] A fourth aspect of the present invention relates to a battery comprising a negative electrode, a positive electrode and a solid electrolyte layer, wherein at least one of the cathode, the anode and the solid electrolyte layer comprises a solid electrolyte according to the present invention. The solid electrolyte of the present invention can be used as a solid electrolyte layer of a solid lithium ion battery or a solid lithium primary battery, or as a solid electrolyte mixed with an electrode mixture for a positive electrode or a negative electrode.
[0161] In a preferred embodiment, the battery is a solid state battery, preferably a lithium solid state battery.
[0162] As understood by those skilled in the art, the negative electrode is the anode and the positive electrode is the cathode. Thus, the present invention relates to a battery comprising a negative electrode, a positive electrode and a solid electrolyte layer, wherein at least one of the positive electrode, the negative electrode and the solid electrolyte layer comprises a solid sulfide electrolyte according to the present invention.
[0163] As understood by those skilled in the art, the solid electrolyte layer is a separator layer or membrane layer separating the anode and cathode from each other.A particularly preferred embodiment is a battery according to the invention wherein the positive electrode comprises a composite positive electrode active material according to the third aspect of the invention.
[0164] A particularly preferred embodiment is a battery according to the invention wherein the positive electrode comprises a further positive electrode active material comprising Li, M' and O, and the solid electrolyte layer comprises a solid electrolyte according to the first aspect of the invention.
[0165] As will be appreciated, the positive electrode as defined herein may comprise a composite positive electrode active material according to the third aspect of the invention and / or may comprise a further positive electrode active material as defined herein, but may additionally comprise other components that are not electrochemically active, in particular conductive agents (such as carbon black) or binders (such as PVDF).
[0166] The other positive electrode active material comprises Li, M' and O, wherein M' comprises one or both of Mn and Co and Ni. Preferably, the positive electrode active material comprises Li, M' and O, wherein M' comprises
[0167] - Ni with a content of x', wherein 50.0mol%≤x'≤95.0mol% relative to M';
[0168] - Mn with a content of y', wherein 0.0mol%≤y'≤40.0mol% relative to M';
[0169] - Co with a content of z', wherein 0.0mol%≤z'≤40.0mol% relative to M';
[0170] - D in an amount a', wherein 0.0 mol% ≤ a' ≤ 2.0 mol% relative to M', wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0171] -wherein x'+y'+z'+ a' is 100.0 mol%;
[0172] More preferably wherein M' comprises:
[0173] - Ni with a content of x', wherein 55.0mol%≤x'≤85.0mol% relative to M';
[0174] - Mn with a content of y', wherein 10.0 mol%≤y'≤30.0 mol% relative to M';
[0175] - Co with a content of z', wherein 10.0mol%≤z'≤30.0mol% relative to M';
[0176] - D in an amount a', wherein 0.0 mol% ≤ a' ≤ 2.0 mol% relative to M', wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0177] -wherein x'+y'+z'+ a' is 100.0 mol%;
[0178] Most preferably wherein M' comprises:
[0179] - Ni with a content of x', wherein 58.0mol%≤x'≤70.0mol% relative to M';
[0180] - Mn with a content of y', wherein 15.0mol%≤y'≤25.0mol% relative to M';
[0181] - Co with a content of z', wherein 15.0mol%≤z'≤25.0mol% relative to M';
[0182] - D in an amount a', wherein 0.0 mol% ≤ a' ≤ 2.0 mol% relative to M', wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0183] - wherein x'+y'+z'+a' is 100.0 mol%.
[0184] In a preferred embodiment of the present invention, D' is at least one element selected from the group consisting of: Al, Ti, B, Ba, Ca, Cr, Fe, Mg, Mo, Nb, S, Si, Sr, V, W, Y, Zn and Zr; preferably Al, B, Ti, Cr, Nb, S, Si, Y, Zr and W; more preferably Al, B, Ti, Nb, Zr and W.
[0185] In some particularly preferred embodiments, a'=0.0 mol%.
[0186] In some particularly preferred embodiments, x' is about 60 mol%, y' is about 20 mol%, and z' is about 20 mol%. This is also known as NMC 622.
[0187] In preferred embodiments, the Li / M' ratio (mol / mol) is between 0.9 and 1.1, preferably between 0.95 and 1.05, more preferably between 0.99 and 1.01, most preferably about 1.
[0188] As will be appreciated by those skilled in the art, the amounts of Li and M in the additional positive electrode active material, preferably Li, Ni, Mn and Co, are measured by inductively coupled plasma optical emission spectroscopy (ICP-OES). For example, but not limited to the present invention, an Agilent ICP 720-ES is used in the ICP-OES analysis.
[0189] In a particularly preferred embodiment, the solid electrolyte layer comprises the solid electrolyte according to the first aspect of the invention. More preferably, the solid electrolyte layer consists of the solid electrolyte according to the first aspect of the invention.
[0190] In a particularly preferred embodiment, the solid electrolyte layer comprises a further solid electrolyte having a composition different from that of the solid electrolyte according to the first aspect of the present invention. Preferably, the further solid electrolyte having a composition different from that of the solid electrolyte according to the present invention is a sulfide solid electrolyte, more preferably, the further solid electrolyte having a composition different from that of the solid electrolyte according to the present invention comprises Li, P and S. Typically, the following sulfur-containing compounds Li6PS5X (wherein X = Cl, Br, I or a combination thereof), sulfo-LISICON (Li 3.25 Ge 0.25 P 0.75 S4), Li2S-P2S5-LiCl, Li2S-SiS2, LiI-Li2S-SiS2, Li2S-P2S5-LiCl, Li2S-SiS2, LiI-Li 2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li2S-P2S5, Li3PS4, Li7P3S 11 , LiI-Li2S-B2S3, Li3PO4-Li2S-SiS2, Li3PO4-Li2S-SiS2, Li3PO4-Li2S-SiS2, Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 and / or Li7P3S 11 Even more preferably, the further solid electrolyte having a different composition than the solid electrolyte according to the invention is an argyrodite-type solid electrolyte, most preferably Li6PS5Cl.
[0191] Therefore, a particularly preferred embodiment is a battery according to the invention in which
[0192] • the positive electrode comprises a composite positive electrode active material as defined herein, and
[0193] • The solid electrolyte layer comprises the solid electrolyte according to the first aspect of the present invention.
[0194] Another particularly preferred embodiment is a battery according to the invention, wherein
[0195] • the positive electrode comprises a composite positive electrode active material as defined herein; and
[0196] • The solid electrolyte layer contains another solid electrolyte having a composition different from that of the solid electrolyte according to the first aspect of the present invention.
[0197] Another particularly preferred embodiment is a battery according to the invention, wherein
[0198] • the positive electrode comprises a further positive electrode active material comprising Li, M' and O as defined herein and a further solid electrolyte having a composition different from the solid electrolyte as defined herein; and
[0199] • The solid electrolyte layer comprises the solid electrolyte according to the first aspect of the present invention.
[0200] A particularly highly preferred embodiment is a battery according to the invention wherein
[0201] • The positive electrode comprises a positive electrode active material comprising Li, M and O, wherein M comprises:
[0202] - Ni with a content of x, wherein 58.0mol%≤x≤70.0mol% relative to M;
[0203] - Mn with a content of y, wherein relative to M, 15.0mol%≤y≤25.0mol%;
[0204] - Co with a content of z, wherein relative to M, 15.0mol%≤z≤25.0mol%;
[0205] - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O;
[0206] - wherein x+y+z+a is 100.0 mol%, and
[0207] comprising a solid electrolyte according to formula (I), wherein 0.4≤y≤0.7, preferably 0.5≤y≤0.7, more preferably 0.55≤y≤0.65; and
[0208] • The solid electrolyte layer comprises a solid electrolyte according to formula (I), wherein 0.4≤y≤0.7, preferably 0.5≤y≤0.7, more preferably 0.55≤y≤0.65.
[0209] A particularly more highly preferred embodiment is a battery according to the invention wherein
[0210] • The positive electrode comprises a positive electrode active material comprising Li, M and O, wherein M comprises:
[0211] - Ni with a content of x=60 mol% relative to M;
[0212] - Mn with a content of y=20 mol% relative to M;
[0213] - Co in an amount z=20 mol% relative to M; and
[0214] comprising a solid electrolyte according to formula (I)f; and
[0215] • wherein the solid electrolyte layer comprises a solid electrolyte according to formula (I)f.
[0216] In a preferred embodiment, the negative electrode comprises a negative electrode active material. Suitable electrochemically active negative electrode materials are those known in the art. For example, the anode may comprise graphite carbon, metallic lithium or a metal alloy comprising lithium (e.g., a Li-In alloy) as a negative electrode active material. Preferably, the negative electrode further comprises a solid sulfide electrolyte according to the first aspect of the present invention and / or another solid electrolyte having a composition different from the solid electrolyte of the first aspect of the present invention as defined herein. Preferably, the other solid electrolyte having a composition different from the solid electrolyte according to the present invention is a sulfide solid electrolyte, more preferably, the other solid electrolyte having a composition different from the solid electrolyte according to the present invention includes Li, P and S, even more preferably, the other solid electrolyte having a composition different from the solid electrolyte according to the present invention is a argyrodite-type solid electrolyte, and most preferably, the other solid electrolyte having a composition different from the solid electrolyte according to the present invention is a argyrodite-type solid electrolyte is Li6PS5Cl.
[0217] In a preferred embodiment, the battery of the present invention has a discharge capacity of at least 150 mAh / g, preferably at least 155 mAh / g, more preferably at least 160 mAh / g. As will be appreciated by those skilled in the art, the discharge capacity is obtained at a C-rate of C / 30 at room temperature over a voltage range of 1.9 V to 3.6 V relative to a LiIn / In reference electrode.
[0218] Method for manufacturing a battery
[0219] A fifth aspect of the present invention relates to a method for manufacturing a battery, preferably a battery according to the fourth aspect of the present invention, the method comprising the following steps:
[0220] (a) providing a positive electrode, preferably a positive electrode as defined herein,
[0221] (b) providing a negative electrode, preferably a negative electrode as defined herein,
[0222] (c) providing a solid electrolyte layer as defined herein,
[0223] (d) Forming a battery by assembling the positive electrode, negative electrode and solid electrolyte layer into a battery.
[0224] A preferred embodiment is a method for making a battery, wherein step (d) comprises forming the battery by pressing the positive electrode, negative electrode and solid electrolyte layer at between 300 MPa and 400 MPa, preferably at about 375 MPa, for 1 minute to 30 minutes, preferably about 5 minutes.
[0225] As will be appreciated by those skilled in the art, all embodiments of the battery according to the fourth aspect of the invention apply mutatis mutandis to the method for manufacturing the battery. For example, various embodiments relating to the composition of the cathode, anode and solid electrolyte layer as explained herein in the context of the battery are equally applicable to the method for manufacturing the battery.
[0226] use
[0227] A sixth aspect of the present invention relates to the use of the solid electrolyte according to the present invention in a battery, preferably a solid-state battery, most preferably a lithium solid-state battery.
[0228] A seventh aspect of the invention relates to the use of a battery according to the invention in any of a portable computer, a tablet computer, a mobile phone, an energy storage system, an electric vehicle or in a hybrid electric vehicle, preferably in an electric vehicle or a hybrid electric vehicle.
[0229] The present invention is further illustrated in the following examples:
[0230] Example
[0231] Description of the test method
[0232] Synthesis scheme
[0233] All synthesis work and sample handling were performed in an Ar-filled glove box with O2 and H2O content <0.1ppm. For each example, stoichiometric ratios of reagents Li2S (Sigma Aldrich, 99.98%), P2S5 (Sigma Aldrich, 99%), LiBr (Alfa Aesar, 99%) and LiCl (Alfa Aesar, 99%) were mixed to obtain a 2g batch of precursor. The precursor was transferred to a Fritsch Pulverisette 7 premium line 80mL zirconia ball mill jar along with 20 10mm diameter zirconia balls (mass ratio of balls to powder was 30:1). The precursor was first milled at 150rpm for 30 minutes to homogenize the mixture, followed by ball milling at 600rpm for a total duration of 20 hours. Each cycle consisted of 15 minutes of milling and 10 minutes of rest, and the milling direction was reversed for each cycle. After every 8 hours of milling, the ball mill jar was opened in the glove box to scrape the material adhering to the lid and to the inside of the jar surface. At the end of the ball milling step, approximately 90% by weight of the material was recovered. The ball milled powder was uniaxially pressed into 10 mm pellets and placed in a pre-dried quartz tube, which was then placed under vacuum (10 -2 mbar) and placed in a furnace (Nabertherm) for annealing. The furnace temperature was slowly increased to 450°C at a heating rate of 1.5°C / min, maintained for 5 hours, and naturally cooled to room temperature. The reacted pellets were then crushed using a pestle and mortar and stored in a glove box for further analysis.
[0234] X-ray diffraction
[0235] Powder X-ray diffraction patterns were collected using a Bruker D8 diffractometer equipped with Cu (Kα1-Kα2) or Mo (Kα1-Kα2) radiation in θ-θ configuration. The measurements were performed using a gas-tight sample holder with a Be window. Patterns were collected between 2θ = 10°-50° with a step size of 0.02°. The Fullprof suite was used for profile matching using the Le Bail method to determine the lattice parameters of the samples.
[0236] Raman spectroscopy
[0237] The spectra were collected using a Raman DXR microscope (Thermo Fischer Scientific) equipped with a green laser with an excitation wavelength of 532 nm. A laser power of 0.1 mW was used to avoid sample damage due to excessive local heating. The spectra were collected with a 1 s exposure time and 180 exposures.
[0238] Ionic conductivity
[0239] About 200mg sample is uniaxially cold pressed at 625MPa in 10mm mold. The relative density of pellets is 85% to 87%, and the thickness is about 1.4mm. Indium foil is pressed on the surface of pellets as ion blocking electrode. AC impedance spectroscopy is performed on them by installing these pellets in BioLogic CESH cell, and 50mV AC perturbation is applied in the frequency range of 30MHz to 1Hz, and spectrum is recorded using MTZ 35 frequency response analyzer. Spectra are collected between -20℃ and 50℃ temperature range in ITS temperature controller with 10℃ intervals. AC impedance data are analyzed using Zview or RelaxIS software.
[0240] Moisture stability
[0241] All measurements were performed on the same day to avoid changes in humidity in the ambient air. H2S sensing experiments were performed in the following setup: approximately 45 mg of powder was granulated in a 10 mm die, and these granules were used for measurement. To start the measurement, the granules were placed on a rectangular polymer container in a desiccator and the lid of the desiccator was closed. H2S values were recorded in ppm every 20 seconds for 20 minutes using an H2S sensor (Model-INS-H 2 S-03 (0ppm-400ppm, 20%-90%RH)). The number of moles of H2S generated per liter of ambient air and per gram of sample was calculated using the following equation:
[0242]
[0243] The right side is multiplied by 10 because the dryer has a volume of 10 L. Assuming that H2S behaves like an ideal gas, the inventors divide both sides by V m , V m is the molar volume of an ideal gas at 1 bar and room temperature (24.79 L.mol -1 ):
[0244]
[0245] Relative to the weight of the sample (m 样品 ) Normalizing both sides results in:
[0246]
[0247] Using this formula, the number of moles of H2S generated per 1L of air and 1g of sample is plotted as a function of time, which is useful for designing larger-scale production and assembly stages. In addition, the reactivity of the S atoms in each material in the presence of moisture is compared. To this end, the number of moles of H2S generated per 1L of air and 1 mole of sample after 15 minutes of exposure is calculated using the following equation:
[0248]
[0249] Among them, MM 样品 is the molar mass of the sample (assuming 100% purity) in g.mol -1 count.
[0250] Example
[0251] Synthesis of solid electrolytes
[0252] Table 1 shows the general formula of the examples synthesized via the general synthesis scheme described above and their corresponding ionic conductivities. It was also observed that EX6 showed 1 mS cm -1 The ionic conductivity of MgO2O3 makes it a very interesting composition for cryogenic applications.
[0253] Profile matching of the powder X-ray diffraction data showed that EX1-7 (space group: F4-3m) retains the argyrodite structure. No peaks corresponding to the precursor or other impurity phases were observed, except for the peak at 2θ = 45.6° from the Be-containing sample holder. Further increase in Cl content (CEX5) leads to the formation of additional impurities (see Figure 1a and Figure 1b ).like Figure 2 As shown, the powder diffraction patterns confirmed the successful synthesis of CEX1-3 and EX5 without any impurities.
[0254] Table 1: Overall formula and ionic conductivity of CEX1-4 and EX1-7 .
[0255]
[0256] The calculated lattice parameter values indicate a linear variation of the lattice constant values with x that follows Vegard's law and confirm the successful preparation of EX1-7. The calculated lattice parameter values were obtained by contour matching using the Le Bail method in the kit, as Figure 3 When Cl is increased - When the content is 2.5447 W, the cubic lattice parameter a gradually decreases from 9.993 Å of CEX4 to 9.908 Å of EX7. Figure 3 shown.
[0257] Raman spectroscopy was performed to further confirm that Cl - Effects of substitutions on the structures of EX1-7 and CEX5. Figure 4a and Figure 4b As shown, the Raman spectra of all samples were -1 There are sharp peaks (ν sym ), accompanied by a -1、268cm -1 、568cm -1 and 593cm -1 Other main peaks at , all of which correspond to different normal modes of PS4 tetrahedron. - The increase in content at 421cm -1 The position of the symmetric stretching mode (ν sym ) gradually moves towards higher wave numbers (cf. Figure 4a and Figure 4b ).
[0258] The H2S evolution measurements were taken for all samples on the same day to keep the relative humidity constant. Figure 5 The amount of H2S released by EX3, EX5 and EX7 in 15 minutes is shown relative to CEX4 and the commercially available argyrodite Li6PS5Cl. Figure 5 As shown in , it is apparent that EX3, EX5, and EX7 have significantly less H2S evolution when compared to commercially available Li6PS5Cl and CEX4.
[0259] Battery Assembly
[0260] 1) Preparation of cathode composite material:
[0261] The cathode composite was prepared by manually grinding 70 wt% NMC-622 and 30 wt% solid electrolyte in an agate mortar and pestle for 20 minutes. No additional conductive carbon was added to the composite.
[0262] 2) Anode composite materials:
[0263] By manually grinding 60:40 weight ratio of Li 0.5 The anode composite was prepared by mixing In alloy and Li6PS5Cl for 1 h until a dark grey powder was obtained.
[0264] 3) Battery assembly:
[0265] A PMMA (polymethyl methacrylate) matrix and two stainless steel pistons with a diameter of 10 mm were used for cell assembly and electrochemical testing. All assembly procedures were performed in a glove box under an argon atmosphere ([O2] < 1 ppm, [H2O] < 1 ppm).
[0266] Assemble the battery as follows:
[0267] a. About 49 mg of solid electrolyte was added to the PMMA matrix and cold pressed under a hydraulic press at 125 MPa for 1 min.
[0268] b. On one side of the solid electrolyte, evenly spread 20 mg to 22 mg of cathode composite material (NMC loading: 14 mg to 15 mg).
[0269] c. On the other side of the solid electrolyte, evenly spread 85 mg of the anode composite material.
[0270] d. The entire stack was compressed at 375 MPa for 5 minutes.
[0271] e. The cells were transferred to a stainless steel frame and a uniaxial stacking pressure of 100 MPa was applied using a torque key.
[0272] f. The entire device was then transferred into a sealed glass jar for further electrochemical testing.
[0273] Electrochemical Cycling Solutions :
[0274] Galvanostatic cycling studies were performed at room temperature in the potential range of 1.9 V-3.6 V relative to the LiIn / In reference electrode. The first charge-discharge cycle was performed at a C rate of C / 30. (C corresponds to 0.6 mol Li per mol active material in 1 hour). It was subsequently cycled at different C rates, including C / 15, C / 10, C / 5, C / 2, and 1C. Each C rate was repeated for a total of 6 cycles. To evaluate the long cycle stability, the cell was subjected to continuous cycling at a C / 5 rate for 50 cycles.
[0275] result :
[0276] Table 2 shows the cathode composite materials including NMC622 and Li 5.4 PS 4.4 BrCl 0.6 ) and the solid electrolyte layer (Li 5.4 PS 4.4 BrCl 0.6 ) and a battery (CEX6) comprising a cathode composite material comprising NMC622 and Li6PS5Cl and a solid electrolyte (Li6PS5Cl).
[0277] Table 2: Specific capacity and retention rate of EX8 and CEX6
[0278]
[0279] Figure 6 and 7 The rate performance and long cycle stability of cells containing cathode composites containing different weight % of NMC-622 and Li 5.4 PS 4.4BrCl 0.6 In these batteries, the solid electrolyte layer is also Li 5.4 PS 4.4 BrCl 0.6 .
Claims
1. A solid electrolyte having a composition according to formula (I): That 6-y P.S. 5-y BrX y (I), where 0.0 < y < 0.8, and X is F, Cl, I, or a combination thereof.
2. The solid electrolyte according to claim 1, wherein 0.05 ≤ y ≤ 0.75, preferably 0.075 ≤ y ≤ 0.725, more preferably 0.1 ≤ y ≤ 0.
7.
3. The solid electrolyte according to claim 1 or 2, wherein X is F, Cl, or I; preferably X is Cl or I; preferably X is Cl.
4. The solid electrolyte according to any one of the preceding claims, wherein 0.4 ≤ y ≤ 0.7, preferably 0.5 ≤ y ≤ 0.7, more preferably 0.55 ≤ y ≤ 0.
65.
5. The solid electrolyte according to any one of the preceding claims, wherein 0.01 ≤ y ≤ 0.59, preferably 0.05 ≤ y ≤ 0.55, more preferably 0.09 ≤ y ≤ 0.
51.
6. The solid electrolyte according to any one of the preceding claims, wherein X is Cl and 0.1 ≤ y ≤ 0.
7.
7. The solid electrolyte according to any one of claims 1 to 3, wherein X is I and 0.0 < y < 0.
4.
8. The solid electrolyte according to claim 7, wherein 0.05 ≤ y ≤ 0.35, preferably 0.075 ≤ y ≤ 0.325, more preferably 0.1 ≤ y ≤ 0.
3.
9. The solid electrolyte according to any one of claims 1 to 6, having a composition according to formula (I) a - g: 。 10. The solid electrolyte according to any one of the preceding claims, having the F - 43m space group, preferably having a lattice parameter a (Å) between 10.00 and 9.90 determined by Rietveld analysis.
11. The solid electrolyte according to any one of the preceding claims, having an ionic conductivity between 1 mS / cm and 12 mS / cm, preferably between 2 mS / cm and 10 mS / cm, more preferably between 6 mS / cm and 10 mS / cm.
12. The solid electrolyte according to any one of the preceding claims, having a purity of at least 90%, preferably at least 95%, more preferably at least 99% as determined by XRD.
13. A solid electrolyte according to any one of the preceding claims, which generates less than 5.0 mmol.L of water after 15 minutes as determined by water stability. -1 .g -1 of H2S.
14. A method for manufacturing a solid electrolyte, preferably the solid electrolyte according to claims 1 to 13, the method comprising the following steps: a) providing a solid electrolyte precursor mixture comprising Li2S, P2S5, LiBr, and LiX; b) mixing the solid electrolyte precursor mixture to obtain a solid electrolyte mixture; and c) heat - treating the solid electrolyte mixture to obtain a solid electrolyte; wherein X is a halogen selected from F, Cl, I, or a combination thereof.
15. The method according to claim 14, wherein the mixing of the solid electrolyte precursor in step b) lasts for at least 0.5 hours.
16. A composite positive electrode active material comprising a positive electrode active material and the solid electrolyte according to any one of claims 1 to 13, wherein the positive electrode active material comprises Li, M and O, wherein M comprises Ni and one or both of Mn and Co.
17. The composite positive electrode active material according to claim 16, wherein M comprises - Ni with a content of x, wherein relative to M, 50.0mol%≤x≤95.0mol%; - Mn with a content of y, wherein 0.0 mol%≤y≤40.0 mol% relative to M; - Co with a content of z, wherein relative to M, 0.0mol%≤z≤40.0mol%; - D in an amount a, wherein 0.0 mol%≤a≤2.0 mol% relative to M, wherein D is at least one element other than Li, Ni, Mn, Co and O; - wherein x+y+z+a is 100.0 mol%. 18 . A battery comprising a negative electrode, a positive electrode, and a solid electrolyte layer, wherein at least one of the positive electrode, the negative electrode, and the solid electrolyte layer contains the solid electrolyte according to claim 1 .
19. The battery according to claim 18, wherein the positive electrode comprises the composite positive electrode active material according to claim 16 or 17. 20 . The battery according to claim 18 , wherein the solid electrolyte layer comprises the solid electrolyte according to claim 1 .
Citation Information
Patent Citations
Solid electrolytes, electronic devices, and methods
WO2020033809A1